Novel insights into the effect of Xiaoyao san on corticosterone-induced hepatic steatosis: inhibition of glucocorticoid receptor/perilipin-2 signaling pathway. Issue 1 (28th February 2022) - Gong, Lian; Wang, Guo-En; Ma, Qing-Yu; Hao, Wen-Zhi; Xian, Min-Hua; Wu, Yan-Ping; Kurihara, Hiroshi; He, Rong-Rong; Chen, Jia-Xu
Abstract: Objective: Xiaoyao san (XYS) is a classic traditional Chinese medicinal formula. It has been clinically administered to regulate liver function. However, its mechanisms in glucocorticoid-induced hepatic steatosis are unknown. This study aimed to investigate whether XYS protects against corticosterone (CORT)-induced hepatic steatosis, and to explore its mechanism. Methods: High-fat diet mice induced with hepatic steatosis by 2 mg/kg CORT were administered 2.56 g/kg or 5.12 g/kg XYS daily for 7 weeks. The effects of XYS on hepatic steatosis in mice were evaluated by H&E and Oil Red O staining and by measuring their plasma lipids (triglyceride, total cholesterol, and free fatty acids). The mechanism of XYS against hepatic steatosis was investigated by network pharmacology, immunohistochemistry, western blotting, and gain-of-function/loss-of-function experiments. Results: XYS alleviated CORT-induced steatosis, decreased plasma lipids, and inhibited glucocorticoid receptor (GR) activation in the liver. Network pharmacology data indicated that XYS may have mitigated hepatic steatosis via GR which mediated adipose differentiation-related protein (ADFP). Gain-of-function/loss-of-function experiments in vitro confirmed that GR positively regulated ADFP expression. Conclusions: XYS ameliorated CORT-induced hepatic steatosis by downregulating the GR/ADFP axis and inhibiting lipid metabolism. Our studies implicate that XYS is promising as a therapy for CORT-induced hepatic steatosis, and lay the foundation for designing novel prophylactic and therapeutic strategies on CORT-induced hepatic steatosis.